СОВЕРШЕНСТВОВАНИЕ ИНТЕЛЛЕКТУАЛЬНОГО ПОДХОДА НА ОСНОВЕ ИННОВАЦИОННЫХ ТЕХНОЛОГИЙ В СИСТЕМЕ ОБРАЗОВАНИЯ - Абдурахманова, А.Т. (SCIENCE and SOCIETY, 2019)
Today one of the important tasks for the teacher in the educational process is teaching the young generation on the basis of increasing their activeness, development of free independent thinking skills and intellectual creative activity. The teacher, dealing with the moral and spiritual education of students, must have the deep knowledge, great skills and the art of teaching himself. Particular attention should be paid to working out of new textbooks, modern pedagogical and information technologies.